Evaluation of life satisfaction and functional fitness of people over 60 years of age living in a nursing home and home environment - Kupcewicz, Ewa; Wróblewska, Teresa; Kędzia, Alina; Wołosewicz, Iwona (Family Medicine & Primary Care Review, 2016)
Background . Life satisfaction may refer to one’s life evaluation, social skills and engagement in life activities. Objectives . Evaluation of life satisfaction and functional fitness of people over 60 years of age living in a nursing home and home environment. Material and methods. A survey research was conducted at the turn of 2013 and 2014 in a group of 101 subjects over 60 years of age. This group comprised of 50 residents of the “Kombatant” nursing home in Ciechanow and 51 subjects staying in a home environment. In the research, the Satisfaction With Life Scale (SWLS ) and Barthel Scale were used. Results. Analysis of the results shows that the mean index of satisfaction with life among all subjects reached 20.7 ± 6.21 with a median of 23, which indicated an average level of satisfaction with life. In a home environment, 50.98% of the subjects reported a high level of satisfaction with life as compared to only 20% in the nursing home. As for evaluation of functional fitness, more than half of the subjects (53.47%) scored 21 to 85 points according to the Barthel Scale, and their condition was determined as “moderate to severe”. A high positive correlation (r = 0.7) was also observed between the functional state described as “moderate to severe” among the subjects staying in a home environment and their satisfaction with life. Conclusions . In the researched group, the level of satisfaction with life varied, with lower results among the residents of the nursing home, whereas for those living in a home environment, functional fitness was the key factor in its determination.